H. G. Wells’s and E. M. Forster’s Transformative Arts: Theoretical Divergences and Formal Connections - Laurent Mellet (Cahiers Victoriens et Edouardiens)
Wells and Forster are usually said to have developed two radically opposed approaches to the power of the arts. I too first set them apart to distinguish between the two main transformative powers of the arts addressed in this issue. Wells’s conviction that the arts could change society and help shape a better, fairer world is famous. In both his essays and novels, Forster regularly considered what is now referred to as intermediality, for instance through his defence of musical forms of ‘rhythm’ and pictorial forms of ‘pattern’ in literature in Aspects of the Novel. Beyond such theoretical divergences, a first common point is to be found in the embedded nature of both concerns in characterisation and plot. In Wells’s Edwardian novels, the only way to fulfil oneself is precisely to try and change the world through political commitment and action, while Forsterian protagonists find salvation in a much more aesthetic progression to sentience. In either case, the novelist questions and experiments with the form of the literary medium. But the narrative and formal modalities of this embeddedness reveal further connections between the two Edwardian artists, since the novels also evince the other transformative power of the arts. Wells’s books sometimes display an interrogation of the novel form in its interconnections with other prose genres (journalism, pamphlet, autobiography), while Forster’s novels often resort to liberal-humanist credos and other democratic stances which read as a plea for another society. These oscillations expose a common conception of prose fiction to reinvent itself but also the world out there which is typically Edwardian, liberal and democratic.